Studies on the chemical composition, digestible energy content and nutritive value of South African grain sorghum (Sorghum vulgare pers) - Brand, Tertius Swanepoel (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1989.